2010
DOI: 10.1016/j.jtcvs.2009.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Is the “sterile cockpit” concept applicable to cardiovascular surgery critical intervals or critical events? The impact of protocol-driven communication during cardiopulmonary bypass

Abstract: Because of wide variations is cognitive workload among caregivers, effective communication can be structured around critical events rather than defined intervals analogous to the sterile cockpit, with reduction in communication breakdowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 13 publications
6
99
0
1
Order By: Relevance
“…In an ideal scenario, effective commu- It is an essential safety barrier that allows error detection and recovery and the opportunity for real-time progress toward a pervasive safety culture. 17 Team members with skills in error detection and recovery perform the time-out in a distraction-free environment. The "sterile cockpit" time-out, even if practiced reluctantly, offers a final opportunity before an invasive procedure for error detection.…”
Section: Discussionmentioning
confidence: 99%
“…In an ideal scenario, effective commu- It is an essential safety barrier that allows error detection and recovery and the opportunity for real-time progress toward a pervasive safety culture. 17 Team members with skills in error detection and recovery perform the time-out in a distraction-free environment. The "sterile cockpit" time-out, even if practiced reluctantly, offers a final opportunity before an invasive procedure for error detection.…”
Section: Discussionmentioning
confidence: 99%
“…Aus diesem Grund wurden Maßnahmen zur Verbesserung der Sicherheit aus anderen Branchen analysiert und Versuche unternommen, sie in den medizinischen Bereich zu übertragen. Vorbild war hauptsächlich die Flugindustrie, aber auch Methoden aus der Formel 1 und der chemischen Industrie wurden über-nommen (Catchpole et al 2007, Wadhera et al 2010 (Henrickson et al 2009). …”
Section: Checklistenunclassified
“…Some have suggested that cardiac surgical operating rooms adopt the ''sterile cockpit'' concept of aviation, where, during takeoff and landings, no conversation other than that pertaining to the critical task at hand is permitted. While this has great appeal, Wadhera et al [41] have demonstrated that the mental workload of each CVOR subteam varies considerably throughout the case, leading to casual conversation among the surgery team just when the anesthesiologist needs absolute quiet (induction/intubation) and vice versa.…”
Section: Disruptions Distractionsmentioning
confidence: 99%
“…Reduction of noise by adopting a ''sterile cockpit'' has been suggested, but Wadhera et al [41] have demonstrated that, unlike aviation, each CVOR team has a different cognitive workload at different stages of the operation. They propose adoption of structured conversations for various stages, but this concept has not been tested.…”
Section: Physical Environment Tools and Technologiesmentioning
confidence: 99%